Cultural practices and politicization of "belonging" (Revista LIDER, 2021)
The article hereby presented gathers philosophical and anthropological elucidations on three aspects of contemporary cultural practices. The first one of this aspects refers to the daily practices which turn into a “disseminated proliferation” of anonymous and perishable humans creations, constituting the enormous abode of contemporary culture. Therefore, this first point concerns to the place assigned by the theoretical speech to the world of the “insignificant”, to the field of the culturally unobserved. The second aspect suggest that the cultural practices theory utopically holds the eventuality of a collective and existential emancipation. This eventuality is given by gestures of political reflections and transgressions which turn out to be the opposite of ideological introspection. Such theory goes to a “politization of the sense of belonging” which permeates the whole of Michel de Certeau´s work. The third aspect which underlies these conceptions, leads to emphasize a humanism of otherness in contrast with the humanism of identity prevailing in twentieth century. The real restoration of this common experience is guided by an emancipative interest which constitutes a political and cultural task of our time.